Uma abordagem para otimização estrutural de rolos de esteiras transportadoras de minérios - Ceniz, João Pedro (2021)
The locomotion of materials with the use of conveyor belts is widely used and is of extreme importance, especially in the mining sector. In order to carry out this type of transport, conveyor systems composed of several rollers are commonly used. The rollers also support the weight of the transported material. The maintenance of this type of component promotes a high annual cost and, when performed, due to the high weight of the product, it might provide risk to the physical integrity of the operator who is responsible for the replacement of the damaged component. As a way of weight reduction, the adoption of polymeric materials in its manufacture, rather than the usual metallic ones, is a possible alternative. Besides, optimization techniques can also be applied for this purpose. In this context, this work proposes to perform the parametric structural optimization of metallic and polymeric rollers using a methodology with the usage of scripts written in the Matlab platform and a numerical model built in commercial finite element code. In the traditional optimization processes, many iterations are often required, which may be impracticable when the evaluation of the objective function and/or constraints have a high computational cost. In order to overcome this drawback, metamodels based on radial base functions (RBF), which are surrogate models to represent a high-cost function, were used herein. Hence, the optimization is performed in the metamodel itself using the Globalized Bounded Nelder-Mead (GBNM), and an iterative process for refining the metamodel. In the present case, the problem is defined as minimizing the mass of the system, which is subject to the constraints of an allowable misalignment angle of the bearings and an allowable stress. The parameters to be changed (the design variables) are the dimensions of the roller and the shaft. With this strategy, it was obtained a decrease of 32.3% in the mass of a metallic roller project and of 18.9% in a polymeric roller, confirming the functionality of the proposed methodology.